Enhanced photoluminescence of LEuH nanosheets: 2D photonic crystals self-assembled by core–shell SiO2@LEuH spheres. Issue 14 (12th March 2019) - Wang, Xinying; Feng, Pingping; Shao, Baiyi; Cui, Fangming; Yang, Xiaojing
Abstract : A two-dimensional (2D) colloidal crystal of core–shell-structured SiO2 @LEuH spheres was prepared and showed enhanced photoluminescence at 611 nm ( 5 D0 → 7 F2 ). Abstract : The enhancement in photoluminescence (PL) is a challenge for layered rare-earth hydroxides, which usually have weak PL due to the quenching effect of hydroxyls. In this work, we provide a strategy to enhance the PL behavior by constructing two-dimensional (2D) photonic crystals. The core–shell structured SiO2 @LEuH spheres were prepared by attaching the positively charged layered europium hydroxide (LEuH) nanosheets onto the negatively charged surfaces of the SiO2 spheres; the core–shell spheres further formed a monolayered 2D colloidal crystal with the hexagonal lattice on a quartz substrate through an evaporation-induced assembly process. The 2D colloidal crystals exhibited a significantly enhanced photoluminescence at 611 nm related to the 5 D0 → 7 F2 transition of Eu 3+ compared with the SiO2 @LEuH spheres and the LEuH nanosheets dispersed in deionized water. The emission band of Eu 3+ hardly changed in the three samples; therefore, the PL enhancement can be attributed to the emission band located at the short edge of the photonic band-gap of the 2D crystals.